Dewetting of Ni Thin Films Obtained by Atomic Layer Deposition Due to the Thermal Reduction Process: Variation of the Thicknesses - Escrig-Murua, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D; Tejo-Lazo, F (Elsevier B.V., 2017)
Nickel oxide thin films with different thicknesses were synthesized by atomic layer deposition. After a thermal reduction process, under a controlled atmosphere of hydrogen, it was possible to convert nickel oxide to metallic nickel. The different thicknesses were obtained for 250 to 2000 cycles of NiCp2/O3. The Ni thin films were characterized by X-ray diffraction, scanning electron microscopy, and by Magneto-Optical Kerr effect measurements. Micromagnetic simulations have been performed to investigate the mechanism of magnetization reversion of these films. Interestingly, the thermal reduction of films synthesized by ALD allows the generation of both randomly oriented, sized and spaced Ni islands and antidot arrays from thin films. © 2017 Elsevier B.V.